Influence of AL Dust Particles on Air Plasma Characteristics in Cathode Sheath - Abbas, Qusay Adnan (University of Thi-Qar Journal of Science, 2014)
The gas discharge–dust particle interaction for a dc discharge in air with micron-sized particles is investigated. The work present illustrated the effect of AL dust particle on current and voltage of discharge and on the radial profile of plasma parameters in the cathode sheath in direct current system. The results shows, the present of dust inside the discharge increases the current while the voltage of discharge decreases. Moreover, the radial profile of plasma characteristics that measure by Langmuir probes in the presence of AL dust shows that the dust changes the plasma characteristics and affects the collective processes in such plasma system. The AL dust is charged positively in the cathode sheath and the plasma potential is negative. The presence of dust did not effect on the electron distrabution in that region.